Power efficient mobile ad-hoc network - Ye, Ming Hua (2008)
Power efficient network protocols attract a lot of research interests in recent years, especially in the mobile communication environment. The intention of our research topic, "Power Efficient Mobile Ad Hoc Network", is to design the communication protocols with power efficiency as a major concern which will increase the operation time of battery-powered mobile communication devices. We proposed modifications to IEEE 802.11 Power Saving Mode to reduce collision probability in the contention period and minimize the time that mobile stations have to stay in active state. Various scheduling mechanisms are proposed and discussed, which can provide a fair and power efficient service for all mobile stations. Probability of collision is greatly reduced through distributed traffic scheduling that insures the data transmission to be contention free. We proposed a hybrid protocol which intelligently chooses the Access Point (AP) assisted DCF (Distributed Coordinator Function) and enhanced PCF (Point Coordinator Function) transmission mechanism of IEEE 802.11 protocol in an infrastructure based wireless LAN environment. We also proposed a more scalable Time Synchronization Function for IEEE 802.11 protocol and enhance the power efficiency by investigating and utilizing the battery recovery effect.